Homocysteinemia: Cause of a Rare Case Coexisting DVT and Recurrent Foetal Loss in Pregnancy - Nidhi Singh1 , Neema Acharya2 , Sourya Acharya3 , Jaya Kore4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Deep vein thrombosis and venous thromboembolism is a major health problem and one of the leading causesof maternal morbidity and mortality Recurrent pregnancy loss either early or late is a serious problem andhas both psychological and physical impact. Thrombophilia are one of the most important causes of DVTas well as Recurrent pregnancy loss as it worsens the physiological hypercoagulable case which exists inpregnancy. Homocysteinemia is rare but an important cause of deep vein thrombosis and recurrent pregnancyloss. Serum homocysteine levels in pregnancy have been linked to preeclampsia,recurrent abortions and lowbirth weight. Diagnosis of this condition is missed on routine basis due to extremely less frequency of theevaluation of serum homocysteine levels on a routine basis. Here we report a case of hyperhomocysteinemiaas underlying cause of bad obstetric history and DVT which are few of the classic presentations of the entityseen in the single patient. the condition was diagnosed by multidisciplinary approach.